Examination of witnesses - Bugarski, Tatjana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
In modern criminal procedure personal evidence is dominant with respect to material evidence and in not a few cases, the verdict is predominantly based on the fact that has been proven by personal evidence. Therefore, both in theory and in law give special attention to such evidence. Examination of witnesses is traditional evidence and also irreplaceable evidence in criminal proceedings to which is given a special attention in this paper work all in the context of entry adversarial elements in our criminal proceedings, primarily on the trial. The paper deals with the issue of burden of proof, as well as basic rules and cross-examination of witnesses at the trial, with special emphasis on cross-examination.
Keywords: criminal procedure; the burden of proof; leading questioning; cross-examination; witnesses